Influence of running velocity on vertical, leg and joint stiffness: Modelling and recommendations for future research - Brughelli, M.; Cronin, J. (Sports Medicine, 2008)
Human running can be modelled as either a spring-mass model or multiple springs in series. A force is required to stretch or compress the spring, and thus stiffness, the variable of interest in this paper, can be calculated from the ratio of this force to the change in spring length. Given the link between force and length change, muscle stiffness and mechanical stiffness have been areas of interest to researchers, clinicians, and strength and conditioning practitioners for many years.